Rosli Dobi / Muhammad Akmal Firdaus Zuhaimi ... [et al.] - Zuhaimi, Muhammad Akmal Firdaus; Abdul Aziz, Muhammad Zarif; Shahferi, Muhammad Amirul; Kamaruddin, Kamarul Idris; Shahrol Ismail, Akif Akmal (2022)
In this business plan, the main parts that are included are Business Description, Marketing Plan, Operation Plan, Administration Plan, Financial Plan, and Business Model Canvas. In our business plan, we have clearly outlined our company and given all of the company's facts that we require. We've given the company's location, as well as a map of our location, together with the company's information. The aim of the business plan is also stated, which is to provide the greatest self-laundry service and apply for the necessary funds. We added their comprehensive profiles in terms of information about our partners in order to introduce our new business owners. In our marketing strategy, we listed all of the marketing methods that will be utilized in our company. We've also included information on the service we offer, our target market, and rivals, as well as market size and share. We went so far as to forecast our company's sales over the following three years. For our sales revenue, this will act as a guideline and benchmark. A marketing budget schedule was also created. This is to ensure that our money is spent correctly and on time. In terms of the operating plan, we developed a working and planning procedure that specifies the workflow for our clients who have used our services. This is to ensure that our customer support procedure runs smoothly and according to the rules. We've also done some planning for production, calculating the expected services for each month, week, and day. A list of suppliers, machineries and equipment, and supplies is also included. We projected the stock purchase after estimating the quantity of stocks for each month throughout the duration of three years. Finally, we estimated the operations budget and produced a project implementation timetable. In the administration plan, we established our company's goals, vision, and mission. The organizational charts have been presented, and they include the jobs of operation manager, marketing manager, administrative manager, and financial manager. We make a list of how many employees there are, what their jobs and responsibilities are, and how much they are paid. We've also provided a list of office equipment needs and a budget for administration. The financial plan includes all of the budgets and costs for each department. The financial plan includes the menu, capital expenditures, pre-operating and working capital predictions, sales and purchase projections, project implementation cost, project financing sources, cash flow, income statement, and balance sheet. Finally, we propose a business model canvas for our company plan (BMC). BMC is a visual tool that emphasizes the value that customers receive. A BMC can help our company remain on top of new opportunities and revenue streams.